PENGARUH ELEMEN PEMBENTUK INTELLECTUAL CAPITAL TERHADAP NILAI PASAR DAN KINERJA KEUANGAN PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Entika, Nova Lili; Ardiyanto, Didik (Diponegoro Journal of Accounting, 2012)
The purpose of this study is to investigate the relation between intellectual capital and firms market value and financial performance on banking company - Return on Equity ( ROE), Return on Assets (ROA) and Growth Revenue (GR). The model that used to measure intellectual capital was using Value Added Intellectual Coefficient (VAIC) or separately-using Capital Employed (VACA), Human Capital (VAHU), and Structural Capital (STVA. This study used 95 banking company data that listed in Indonesia Stock Exchange (IDX) for five years 2006-2010. This study used multiple linear regression for data analysis. The results showed that intellectual capital (VAIC) has an impact to firms market value and financial performance (ROA and, ROE). VACA and STVA have a positive impact to the market value (MtBV) and financial performance (ROE and ROA) while VAHU has no impact on firms market value ( MtBV) and negatively affects on ROE.